Constructing Norms of Body Mass Index, Fat Percent, Lean Body Weight, Body ‎Surface Area and Resting Metabolic Rate of Female Physical Education Majors - Abed Elnaser Al-Qadomi; Subhi Nemr (My University, 2005)
The purpose of this study was to construct norms of Body Mass Index (BMI), Fat Percent (% Fat), Lean Body Weight (LBW), Body Surface Area (BSA) and Resting Metabolic Rate (RMR) of female physical education majors at An-Najah National University. Furthermore, determine the correlation coefficient among (BMI, % Fat, LBW, BSA and weight (WT) with RMR. The sample consisted of all female physical education majors’ (62) students, Tanita TBF-410 Bioelectrical impedance analyzer (BIA) was used to determine variables. The results revealed that the means of BMI, % Fat, LBW, BSA (WT) and RMR were respectively: (22.46 kg/m2, 24.15%, 44.19 kg, 1.6211 m2, 58.97 kg, and 1427.95 kcal/day), and the best percentile ranks are respectively: (19.30kg/m2, 17%, 47.21 kg, 1.76m2, 1560 kcal/day). In addition, the results revealed a significant positive correlation between BMI, LBW, BSA (WT) and RMR, and negative correlation between % fat and age with RMR. Also, the results of Regression (R2) contribute in developing three equations for the prediction of RMR, using WT, BSA, and LBW as predictors, the best predictor was WT where (R2) was (0.971), the equations were as follow: RMR kcal/day=834,824 + WT * 10,58 RMR kcal/day=266,487 + BSA + 716,466 RMR kcal/day=146,294 + LBW * 29,001

هدفت الدراسة إلى بناء مستويات معيارية لمؤشر كتلة الجسم ونسبة الدهن ووزن العضلات ومساحة سطح الجسم والتمثيل الغذائي خلال الراحة لدى طالبات تخصص التربية الرياضية في جامعة النجاح الوطنية، إضافة إلى معرفة العلاقة بين متغيرات مؤشر كتلة الجسم ونسبة الدهن ووزن العضلات ومساحة سطح الجسم مع التمثيل الغذائي خلال الراحة لدى طالبات تخصص التربية الرياضية في جامعة النجاح الوطنية، لتحقيق ذلك أجريت الدراسة على جميع الطالبات من مختلف السنوات الدراسية والبالغ عددهن (62) طالبة، وكانت متوسطات العمر، والطول، والوزن، ومؤشر كتلة الجسم، ومساحة سطح الجسم، ونسبة الدهن، ووزن العضلات، والتمثيل الغذائي خلال الراحة على التوالي: (20.25سنة، 1.61متر،58.97 كغم، 22.46كغم/م2، 1.62 م2،24.15 %، 44.19كغم،1427.95سعر/يوميا) وكانت أفضل الرتب المئينية لمتغيرات مؤشر كتلة الجسم، ومساحة سطح الجسم، ونسبة الدهن، ووزن العضلات، والتمثيل الغذائي خلال الراحة على التوالي: (19.30كغم/م2، 1.76 م2، 17%، 47.21كغم،1559سعر/يوميا)، ولغاية جمع البيانات استخدم جهاز (Tanita TBF-410)،كما تم التوصل باستخدام معامل الانحدار إلى ثلاث معدلات للتنبؤ بقياس التمثيل الغذائي خلال الراحة وكانت أفضل معادلة باستخدام وزن الجسم حيث وصلت قيمة (R2) إلى (0.971)، وفيما يتعلق بالمعادلات الثلاث كانت على النحو الآتي: سعر/يومياً= 834,824 + وزن الجسم * 10,058 RMR سعر/يومياً= 266,487 + مساحة سطح الجسم * 716,466 RMR سعر/يومياً= 146,294 + وزن العضلات * 29,001 RMR
بناء مستويات معيارية لمؤشر كتلة الجسم ونسبة الدهن ووزن العضلات ومساحة سطح ‏الجسم والتمثيل الغذائي خلال الراحة لدى طالبات تخصص التربية الرياضية‏